2011
DOI: 10.1111/j.1600-0501.2011.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in arterial supply to the floor of the mouth and assessment of relative hemorrhage risk in implant surgery

Abstract: Susceptibility of the submental artery in type II, III, and IV to injury during implant surgery is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 22 publications
0
50
0
2
Order By: Relevance
“…As regards the arterial pattern alterations, the tooth loss resulting in a shift from a centrifugal to a centripetal blood circulation and the preservation of involved tissues is essential in edentulous mandibles [8]. Due to the decrease of mandibular height, the mylohyoid muscle reaches the AC and the intervening surgeon apart from the arteries and structures located in the sublingual space should be alert of those below the mylohyoid muscle [8,9]. Another complication related to the content of MLF and LLF, caused during dental implants placement, is the sensory disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the arterial pattern alterations, the tooth loss resulting in a shift from a centrifugal to a centripetal blood circulation and the preservation of involved tissues is essential in edentulous mandibles [8]. Due to the decrease of mandibular height, the mylohyoid muscle reaches the AC and the intervening surgeon apart from the arteries and structures located in the sublingual space should be alert of those below the mylohyoid muscle [8,9]. Another complication related to the content of MLF and LLF, caused during dental implants placement, is the sensory disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…The sublingual artery is in high risk of laceration and transection when courses horizontally between the sublingual fossa and the mandible [9,15]. The injury of the submental artery may occur when its branches enter the sublingual space perforating the mylohyoid muscle or take a roundabout course near the mandibular surface [9]. The sublingual artery enters through the lingual canal at an average height of 10.3 mm from the LBM [15] and its diameter and the average blood flow are sufficient to cause a life-threatening haemorrhage [15,16,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the sublingual artery that branches from the lingual artery, and the submental artery from the facial artery, run antero-posteriorly above and below the mylohyoid muscle, respectively 4 ; however, there are variations in their courses. 5,6 Hofschneider et al 7 reported that 71% of specimens had a sublingual artery in the mandibular anterior region, while 41% had a branch of the submental artery perforating the mylohyoid muscle into the same region. On the other hand, Bavitz et al 8 found that a perforating submental artery was present in 60% of the cases, while the sublingual artery was small or missing in 53% of the cases.…”
mentioning
confidence: 99%
“…As several authors reported on life-threatening hemorrhage in the floor of the mouth subsequent to implant placement in the mental interforaminal region [13][14][15][16]. Therefore, some reports have suggested a relationship between such a surgical incident and the presence of genial spinal (lingual) foramina [4,15,17,18].…”
Section: Introductionmentioning
confidence: 99%